2021
DOI: 10.1371/journal.pone.0258468
|View full text |Cite
|
Sign up to set email alerts
|

Association between antenatal care utilization pattern and timely initiation of postnatal care checkup: Analysis of 2016 Ethiopian Demographic and Health Survey

Abstract: Background Despite significant public health intervention, maternal mortality remains high in low- and middle-income countries, including Ethiopia. Effective postnatal care is a critical service to reduce maternal mortality. In Ethiopia, only 17% of mothers received postnatal care services in 2016. Objective This study examined the association between antenatal care and timely postnatal care checkup among reproductive-age women in Ethiopia. Methods The study used the 2016 Ethiopian Demographic and Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This study also revealed that the odds of PNC service utilization among women who gave birth at a health facility were 5.91-fold higher compared to women who delivered their last birth at home. This finding is consistent with the findings of the studies conducted in different parts of Ethiopia ( 20 , 24 , 27 , 28 , 30 , 33 ), and various areas in Sub-Saharan African countries ( 34 ). The possible explanation is that women who give birth in health facilities have a better opportunity to get health education regarding postnatal care services and have access to benefits and availability of PNC services during their stay in health facilities.…”
Section: Discussionsupporting
confidence: 92%
“…This study also revealed that the odds of PNC service utilization among women who gave birth at a health facility were 5.91-fold higher compared to women who delivered their last birth at home. This finding is consistent with the findings of the studies conducted in different parts of Ethiopia ( 20 , 24 , 27 , 28 , 30 , 33 ), and various areas in Sub-Saharan African countries ( 34 ). The possible explanation is that women who give birth in health facilities have a better opportunity to get health education regarding postnatal care services and have access to benefits and availability of PNC services during their stay in health facilities.…”
Section: Discussionsupporting
confidence: 92%
“…Severe anaemia can lead to foetal heart failure, fluid retention and swelling (hydrops), and intrauterine death. Before birth, anaemia and hydrops can be managed with intrauterine transfusions, but this carries a 2% risk of foetal loss [182].…”
Section: Evidence-based Management Of Rhesus Negative Pregnancy and P...mentioning
confidence: 99%